Analysis of the Dependencies and Trade Advantages between Lao PDR and China under the Status of the COVID-19 - SIOUDOMPHAN, Soutthavone; SONESAI, Khamsone; PHOMMANY , Sombath; INTHAVICHIT, Lattana (Souphanouvong University Journal Multidisciplinary Research and Development, 2022)
This research aims to analyze the dependencies and trade advantages between the Lao PDR and China under the status of the COVID-19. The data was analyzed using Multiple Regression Analysis to find the important factors affecting trade dependencies and to force the trade dependencies between Lao PDR and China in the future. The results of this study revealed that the Lao PDR had an average trade dependency with China of 29,94 percent. In addition, the average export dependency was 15,34 percent, and the average import dependency was 14.60 percent. Minerals, livestock, cereals, natural gas, vegetables, fruits, beans, coffee, tea, rubber, and wood products are among the 9 types of goods that have comparative advantages in exports, while the export of machinery and electrical equipment is relatively disadvantageous. The factors that affect trade dependencies between Lao PDR and China include five factors, such as: GDP of Laos will result in a decrease in trade dependence between Lao PDR and China; the value of China investment in Lao PDR will result in an increase in trade dependence between Lao PDR and China; the value of foreign investment in Lao PDR will result in an increase in trade dependence between Lao PDR and China with the confidence level of 99%; the foreign exchange rate result in an increase in trade dependence between Lao PDR and China; and the inflation will result in an increase in trade dependence between Lao PDR and China with a confidence level of 99%. At the same time, the trend of trade dependency between Lao PDR and China will increase in the future. The trade in the 2021–2025 period will experience continuous growth and increase every year, expected to increase from 31.61 percent in 2021 to 33.86 percent in 2025, while the trend of exports to China is also increasing, such as the export dependence rate of 17,40 percent in 2021, which is expected to increase to 19.99 percent in 2025, while the dependence trend on imports from China is likely to increase at a steady rate of 16.22 percent per year.